2013
DOI: 10.1016/j.jeem.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of indirect land-use change: Empirical evidence from Brazil

Abstract: The expansion of a given land use may affect deforestation directly if forests are cleared to free land for this use, or indirectly, via the displacement of other landuse activities from non-forest areas towards the forest frontier. Unlike direct land conversion, indirect land-use changes affecting deforestation are not immediately observable. They require the linking of changes occurring in different regions. This paper empirically estimates these indirect effects for the case of Brazil. It presents evidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 22 publications
1
41
0
2
Order By: Relevance
“…Andrade de Sá et al (2013) show that a necessary condition for displacement is that the output of the displaced activity faces a relatively inelastic demand, which might be the case, for instance, if the displaced crop is a staple food produced and consumed locally, or if the country is a major producer and exporter such that its supply affects international prices.…”
Section: Box 1 Zoning Policies For Sugarcane Expansionmentioning
confidence: 99%
See 3 more Smart Citations
“…Andrade de Sá et al (2013) show that a necessary condition for displacement is that the output of the displaced activity faces a relatively inelastic demand, which might be the case, for instance, if the displaced crop is a staple food produced and consumed locally, or if the country is a major producer and exporter such that its supply affects international prices.…”
Section: Box 1 Zoning Policies For Sugarcane Expansionmentioning
confidence: 99%
“…(Lapola et al 2010;Arima et al 2011;Andrade de Sá et al 2013;Correa 2013). Other studies have pointed to recent deforestation in the Cerrado biome due to soybean and pasture expansion farther east and northeast in the biome, particularly in the States of Bahia, Maranhão, Piauí and Tocantins (Brannstrom 2009;IBGE 2013), although it is unclear whether these trends reflect iLUC from the southern Amazon.…”
Section: Program For Combating Deforestation and Forest Fires In The mentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, iLUC are the theoretical changes in land use that take place as a consequence of a bioenergy project, but are geographically disconnected to it (Berndes, Ahlgren, Börjesson, & Cowie, 2013). Some studies used land use statistics and models to find empirical evidence of iLUC due to biofuel production (Arima, Richards, Walker, and Caldas (2011), Andrade de Sá, Palmer, and di Falco (2013) and Jusys (2017). These studies, which have a Brazilian focus, found that indirect changes often occur in close proximity to the biofuel raw material production.…”
Section: Introductionmentioning
confidence: 99%